2017
DOI: 10.1038/s41598-017-07194-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin I suppresses human osteosarcoma growth by inactivation of Wnt/β-catenin pathway in vitro and in vivo

Abstract: Osteosarcoma is the most common primary bone cancer in children and adolescents. In spite of aggressive treatment, osteosarcoma has a high mortality rate with minimal improvements in survival over past few decades. Polyphyllin I (PPI), a component in the traditional Chinese medicinal herb Paris polyphylla Smith, has been shown to have anti-tumor properties. However, its mechanism as an anti-osteosarcoma agent has not been well elucidated. In this study, we found that PPI suppressed osteosarcoma cell viability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…The compound was found to suppress in vitro growth of osteosarcoma 143-B and HOS cells, as well as the primary cells from a osteosarcoma patient and, what is more important, inhibited in vivo intratibial primary tumor growth in xenograft orthotopic mouse model. Moreover, it induced cell apoptosis, cell cycle arrest and inhibited the invasion and migration of osteosarcoma cells (Chang et al 2017). Other interesting effects were obtained in the studies on concomitant administration of PPI with other compounds, including currently used chemotherapeutics.…”
Section: Results Of In Vivo Studiesmentioning
confidence: 93%
“…The compound was found to suppress in vitro growth of osteosarcoma 143-B and HOS cells, as well as the primary cells from a osteosarcoma patient and, what is more important, inhibited in vivo intratibial primary tumor growth in xenograft orthotopic mouse model. Moreover, it induced cell apoptosis, cell cycle arrest and inhibited the invasion and migration of osteosarcoma cells (Chang et al 2017). Other interesting effects were obtained in the studies on concomitant administration of PPI with other compounds, including currently used chemotherapeutics.…”
Section: Results Of In Vivo Studiesmentioning
confidence: 93%
“…Previous studies, including ours, showed that PPI inhibited growth and induced cell cycle arrest, and apoptosis of human cancer cells [12,14,15]. In the current study, we examined the potential synergy of the combination of PPI and enzalutamide in this process.…”
Section: Combination Of Ppi and Enzalutamide Further Inhibited Growthmentioning
confidence: 99%
“…PPI also demonstrated anti-tumor activity on ovarian cancer in vivo via modulation of caspase-9, c-Jun, and secreted glycoprotein Wnt5a [13]. Moreover, PPI suppressed growth, induced apoptosis, and inhibited the invasion and migration of osteosarcoma cells by inactivating the Wnt/β-catenin pathway both in vitro and in vivo [14]. We previously showed that PPI inhibited the growth of human lung cancer cells via stress-activated protein kinase/c-Jun N-terminal kinase-mediated inhibition of the protein expression of the nuclear factor-kappaB (NF-κB) subunit p65 and DNA methyltransferase 1.…”
Section: Introductionmentioning
confidence: 98%
“…However, approximately 40% of OS patients have been found to have metastasized at the time of initial diagnosis, which poses a serious challenge to patient prognosis and long-term survival. 2 Therefore, early diagnosis and treatment of OS is critical to improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%